Strategi Tiongkok dalam Memanfaatkan Momentum Kebijakan Larangan Ekspor Bijih Nikel oleh Pemerintah Indonesia - Riedho, M Roehman Zainur (Jurnal Ilmiah Hubungan Internasional, 2024)
The Indonesian government has enforced a prohibition on nickel ore exports since 2020. This study aims to illuminate China's strategic approach in capitalizing on this situation. China's strategy aligns its national interests with the domestic demand for nickel. Analytically, the framework of national interests sheds light on how Indonesia and China collaborate to satisfy their respective priorities mutually. China requires nickel supplies from Indonesia and seeks Chinese investment for Indonesia's nickel downstream initiatives. Employing a descriptive qualitative research design, this study draws upon secondary data sources to examine Chinese companies operating in Indonesia. While not all companies have websites, the research reveals that China leverages the momentum created by Indonesia's nickel export tires by investing in and expanding joint ventures with Chinese enterprises. China secures profits through these investments and business expansions while meeting its domestic nickel demand via imports from Indonesia. These joint ventures operate in industrial zones designated by the Indonesian government and are often funded by Chinese banks. This strategic interplay serves as a political tool for the Chinese government, leveraging its economic power and capital for broader national interests. Simultaneously, Indonesia wields its control over the world's largest nickel reserves to attract Chinese companies to invest in the nickel processing and refining sector within its borders.   Keywords: Indonesia; National Interest; Tiongkok; Nickel; Export ban